2015
DOI: 10.1007/s13238-015-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

The physiological role of drug transporters

Abstract: Transporters comprise the largest family of membrane proteins in human organism, including members of solute carrier transporter and ATP-binding cassette transporter families. They play pivotal roles in the absorption, distribution and excretion of xenobiotic and endogenous molecules. Transporters are widely expressed in various human tissues and are routinely evaluated during the process of drug development and approval. Over the past decade, increasing evidence shows that drug transporters are important in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 88 publications
0
56
1
3
Order By: Relevance
“…Traditionally, radio-isotopically labelled drugs would be used, but nowadays fluorescent assays (e.g. [216][217][218][219][220]) or mass spectrometric assays [221] are more common.…”
Section: Figure 3 An Untargeted Metabolomics Strategy For Determininmentioning
confidence: 99%
“…Traditionally, radio-isotopically labelled drugs would be used, but nowadays fluorescent assays (e.g. [216][217][218][219][220]) or mass spectrometric assays [221] are more common.…”
Section: Figure 3 An Untargeted Metabolomics Strategy For Determininmentioning
confidence: 99%
“…More intriguingly, we also identified a few genes related to drug transportation in puromycin screening (Fig. 2F) (Liang et al, 2015). Moreover, GO analysis of puromycin resistant genes revealed that there was a significant enrichment in the terms of intracellular signal transduction, endocytosis, and components of the membrane (Figs.…”
Section: Cellmentioning
confidence: 71%
“…The alteration of ADME characteristics during inflammation can often be attributed to an enzymatic change in drug metabolism. The decrease in the expression of CYP450, which is the primary drug metabolizing enzyme in the liver, following inflammation would be an example of this [9]. …”
Section: Drug Metabolism In Clinical Human Pharmacologymentioning
confidence: 99%
“…Tissue-specific extracts from liver or muscle can be utilized to investigate the role of a transporter in energy related metabolism [9]. Common transporters involved with the alteration of a drug’s ADME consists of P-gp, BCRP, OATP1B1/1B3, OAT1/3, OCT1 and OCT2 [10].…”
Section: Drug Metabolism In Clinical Human Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation